Comparative Study for Risk Criteria of Al-Qudus Plant between the Present and Planning of MOE (Journal of Engineering, 2014)
The main function of a power system is to supply the customer load demands as economically as possible. Risk criterion is the probability of not meeting the load. This paper presents a methodology to assess probabilistic risk criteria of Al-Qudus plant before and after expansion; as this plant consists of ten generating units presently and the Ministry Of Electricity (MOE) is intending to compact four units to it in order to improve the performance of Iraqi power system especially at Baghdad region. The assessment is calculated by a program using Matlab programming language; version 7.6. Results show that the planned risk is (0.003095) that is (35 times) less than that in the present plant risk; (0.1091); which represents respectable improvement. This probabilistic method can also be used to find the planned risk level of every plant to be compact in the Iraqi electrical network on the future; or any other power systems; and compare it with the present criterion which is very useful to determine the necessary generation capacity expansion.